STRATEGI BELAJAR BAHASA ARAB MAHASISWA PRODI PBA IAIN ANTASARI BANJARMASIN MENURUT MODEL OXFORD - Muradi, Ahmad; Hasbullah, Hasbullah (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2016)
This research is a case against of departement of Arabic education of IAIN Antasari Banjarmasin to learn Arabic. The data source of this research is the student of 2012/2013, 2013/2014, and six lecturers that administer of linguistic subject or language skills. This study aims to collect information on students learning Arabic strategies in departement of Arabic education. While the data extracted is information about: the form of difficulty students learning Arabic, the cause and degree of difficulty, the type of student learning in departement of arabic education, the efforts and strategies by departement of arabic education students in problem solving learning Arabic, and the outcome of the efforts/strategies they are doing. Based on the survey results revealed that students have difficulty in learning Arabic in the matter of language and language skills. Difficulties in linguistic materials include use nahwu and sharf in reading and writing, the meaning of a sentence or a word, sentence or word and pronunciation. While the difficulties in aspects of language skills include: listening, speaking, reading, and writing. But the difficulties they feel it, both aspects of alkalinity or their skills can be overcome by evaluating their learning, the dominant use of memory strategies, affective, cognitive, and social strategies.